2016
DOI: 10.1093/ndt/gfw340
|View full text |Cite
|
Sign up to set email alerts
|

Klotho suppresses the renin-angiotensin system in adriamycin nephropathy

Abstract: Our data indicate that Wnt is involved in the pathogenesis of adriamycin nephropathy. Furthermore, klotho supplementation inhibited Wnt signaling, ameliorating renal angiotensin II. Finally, klotho protein appears to suppress epithelial-mesenchymal transition by inhibiting TGF-β and Wnt signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…32 The excretion of PGF2α represents an index of oxidative stress. 6,7 Thus, these findings suggested that klotho-induced decrease in renal Ang II levels and oxidative stress contributed to the decrements of HIF-1α abundance. Wang et al 15 showed that Ang II induced profibrotic changes by activating HIF-1α in medullary fibroblasts.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…32 The excretion of PGF2α represents an index of oxidative stress. 6,7 Thus, these findings suggested that klotho-induced decrease in renal Ang II levels and oxidative stress contributed to the decrements of HIF-1α abundance. Wang et al 15 showed that Ang II induced profibrotic changes by activating HIF-1α in medullary fibroblasts.…”
Section: Discussionmentioning
confidence: 80%
“…Klotho protein supplementation substantially increased renal klotho expression (Figure 4D) and elevated both serum klotho levels and urinary klotho excretion (Figure 4E and 4F) to the levels similar to normotensive control rats. 6 Of note, klotho supplementation failed to alter serum calcium, phosphate, and FGF23 levels in this model (Table S2). Early phase of kidney disease model may relate to small effects of klotho supplementation on mineral metabolism.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations